Model Pariwisata Berkelanjutan (Sustainability Tourism) dan Dampaknya terhadap Pembangunan Ekonomi Masyarakat di Desa Senaru Kabupaten Lombok Utara - M. Sya'ban; Muslihun; Muh. Azkar (Mutawasith: Jurnal Hukum Islam, 2025)
This study aims to analyze the sustainable tourism model in Senaru Tourism Village, North Lombok, and its contribution to the local community's economic development. Using a qualitative approach and phenomenological method, this research explores the direct experiences of tourism actors, including the village head, members of the Tourism Awareness Group (Pokdarwis), and local residents involved in tourism activities. Data was collected through in-depth interviews, non-participatory observation, and documentation. The findings indicate that sustainable tourism in Senaru not only increases income and job opportunities but also enhances quality of life through infrastructure development and community training. By integrating social, cultural, and environmental aspects, tourism in Senaru successfully balances economic benefits with environmental preservation. This study contributes to a deeper understanding of sustainable tourism implementation and its impact on local welfare, offering practical insights for similar tourism development models in other regions.